Analisis Sektor Basis Perikanan dan Komoditas Unggulan di Kabupaten Karimun - Ismu Kusumanto; FNU anwardi; Pitriya Anggeon Sari; Wresni Anggraini; FNU Nofirza (Universitas Katolik Parahyangan, 2019)
Karimun Regency is the one of the regions that is in the development of increasing economic growth and has considerable business opportunities to increase regional economic growth. Karimun regency has natural resources that are still very potential to be developed. Business sector distribution indicators to see the rate of economic growth can be indicated by the number of Gross Regional Domestic Product, indicate that the average growth of the economic sector that provides a largest distrbution from 2010-2017 is the agriculture, forestry and fisheries sector which is equal to 17,05% and subsector which provides the largest distribution is the fisheries sector in the amount of 71,61%. However, from 2010-2017 the agriculturue, forestry and fisheries sector experienced a slowdown in economic growth of 2,76%. This research aims to analyze the base sector in the fisheries sector using the approach Location Quotient (LQ) method, afterwards the sector which is the potential sector or base is analyzed using the approach Analytical Hierarchy Process (AHP) to determine the leading commodities in the base sector. Results of this research indicate that the sector is the base sector and the main concern of the regional government in increasing regional economic growth in the fisheries sector is the capture fisheries subsector with the value of LQ > 1, that is 1,32 and the leading commodities in the capture fisheries subsector are cuttlefish with a growth of 0,40 the followed by large pelagic fish 0,30 andthen shrimp commodities of 0,17 and the last is small pelagic fish of 0,12.Keywords : Regional Economic Growth, Fisheries Sector, Location Quotient, Analytical Hierarchy Process